The diabetic diet : education, compliance and practical applications - Smith, Cynthia J (Division of Endocrinology and Diabetology, 2017)
The aim of this thesis is to investigate different methods of improving the glycaemic control of diabetic out-patients, within the scope of the author's training both as a therapeutic dietitian and as a teacher. Evidence is presented from the literature, which indicates that high-carbohydrate, high-fibre diets are of benefit in diabetes, that supplements of viscous fibre improve glycaemic control, and that education of the diabetic patient may help to achieve good diabetic control, provided that the patient also complies with all parameters of therapy. Three main studies have been undertaken: - (1) An educational project, to investigate the effect of a mass-education programme on compliance and control in diabetic out-patients. (2) An investigation of the effect of long-term high-fibre diets in diabetic out-patients. (3) A study of the use of guar gum in the diabetic diet. In Study 1, a large random sample of patients attending a diabetes outpatient clinic were tested by means of a detailed questionnaire, in order to assess their existing knowledge of the disease. A suitable education programme was then devised and patients were exposed to this in the clinic situation. Another sample of patients was then re-tested with the same questionnaire and statistical analysis was used to assess the effect of this programme on knowledge, compliance and control. Results indicate that, while patients' knowledge scores improved, there was no improvement in dietary compliance and also no significant change in the standard of diabetic control in the clinic population. In Study 2 we investigated the practical aspects of administering a high-fibre diet to diabetic out-patients in Cape Town, in the light of the reported benefits of diets containing large amounts of dietary fibre (OF) in the control of diabetes. Readily-available, low-cost foodstuffs with a high OF content, were incorporated into suitable, individualised high-fibre meal plans for 10 selected diabetic out-patients. Patients were closely monitored over a period of 9 months, for 3 months of which the high-fibre diet was prescribed. Various parameters of glycaemic control were recorded and analysed, and the patients' compliance to the new regimen was assessed. Only 3 patients approached the projected fibre intake, but significant negative correlations were found between the dietary fibre increments and both mean plasma glucose and mean serum triglyceride changes. These findings suggest that, were it not for poor dietary compliance, a high-fibre diet might result in significant improvement in diabetic control, and that education and motivation are of prime importance when making major changes to patients' eating habits. Study 3 investigates the use of guar gum, when incorporated into the diabetic diet in both short- and medium-term studies. This viscous fibre has been shown by workers overseas to be effective in lowering postprandial glycaemia. In this study a palatable vehicle for the gum, a digestive-type biscuit, was tested for its effect on glycaemic control when incorporated into the usual meal plans of diabetic out-patients, and also against an oral glucose load as a reference standard. It was found to be effective in reducing the post-prandial rise in blood glucose, and in improving glycaemic control, as shown by reduced fasting blood glucose values and decreased 24-hour urinary glucose excretion. The biscuit proved to be palatable and acceptable to patients, and the guar gum was effective in much smaller quantities than have previously been tested. It may therefore prove a valuable adjunct to diabetes therapy. Results of these studies indicate that compliance to therapeutic recommendations is the crux of achieving good diabetic control. Increased diabetic knowledge alone does not lead to improved diabetic control, and compliance to altered eating habits is difficult to achieve unless prior education and motivation has taken place. The simplest means of achieving better glycaemic control of diabetes appears to be the use of a supplement of viscous fibre, which will improve the glycaemic response to the patients' usual meals.